Effect of decellularization process on the echanical properties of porcine coronary artery - Lilianty, Riang (2008)
In an attempt to develop an extracellular matrix (ECM) for the engineering of coronary artery, the mechanical properties of porcine coronary arteries were investigated. The effects of two decellularization agents, 0.1 % Sodium Dodecyl Sulfate (SDS) and 0.1% Trypsin/0.02% EDTA (T/E) on the removal of cellular components from these arteries were investigated. Scanning Electron Microscopy and uniaxial tensile test were employed to analyze the structural and mechanical properties. There were no significant differences in terms of wall thickness, load-bearing property, UTS , tissue modulus, failure strain and extensibility between the native left and right coronary arteries harvested from hearts of different sizes. This suggests that the weight of pigs, size of porcine hearts, and origin of porcine coronary arteries have no effect on the mechanical properties of coronary arteries. Both SDS and T/E treatments, on native tubular arteries, performed at 37°C for 24 hours under permanent shaking, were found not able to remove cells completely, in particular the luminal side, but led to alteration of matrix. All treated arteries have reduced load-bearing properties and possess lower UTS and tissue modulus compared to fresh arteries. Disordered, fibrous mesh structures were observed in matrix after SDS treatment while loose collagen bundles were observed in matrixafter T/E treatment. Between these two matrices, T/E-treated matrix showed a tissue modulus closer to that of the fresh arteries. These observations suggest that T/E-treated arteries are stronger than SDS-treated arteries and T/E treatment preserves the ECM proteins such as collagen and elastin better than SDS treatment.